IMPLEMENTASI PATROLI PARADIGMA BARU GUNA MENCEGAH TINDAK PIDANA CURAT DI CIAMIS - Yehezkiel Surya Ningrat Damanik (Police Studies Review, 2017)
In 2019, based on data obtained from the Ciamis District Police Criminal Unit, the highest crime was theft by weighting with 69 cases. This is certainly very worrying for the people in Ciamis Regency for their safety. This is of course the responsibility of the police, bearing in mind the duties and main functions of the police, namely maintaining security and public order as stipulated in Law No.2 of 2002 concerning the Indonesian National Police. Therefore, the Ciamis Regional Police took a preventive measure in the form of police patrol which was carried out by the Sabhara technical functions. The research, which is located in Ciamis Regency, West Java, aims to describe the implementation of patrols carried out by patrol units in Sabhara Ciamis Police Unit, describe the supporting and inhibiting factors of patrol implementation, and then describe the appropriate patrol method to prevent criminal acts of deterrence by weighting at the Ciamis Police Unit. Ciamis region. This study uses qualitative methods with descriptive research types and uses data triangulation (Moeloeng, 2016: 330). Sources of data owned are primary and secondary data sources and data validity that is data presentation. This study uses management factor theory and intellectual competency theory, as well as new paradigm patrol concepts and weight theft concepts. In its implementation, patrol is implemented less than optimal and there are several supporting and inhibiting factors in the implementation of patrol, this is assessed by the theory used. The conclusion is that the implementation of patrols is not optimal, the inhibiting factor is the competence of members, and the right patrol is the dialogic Patrol method.